Mortality in Greenlanders with chronic hepatitis B virus infection - Krarup, Henrik B.; Rex, Karsten F.; Andersen, Stig (Journal of viral hepatitis, 2022)
In‐depth reviewing of all medical records and clinical databases concluded a 7‐year shorter lifespan among Greenlanders infected with hepatitis B virus (HBV) compared with non‐infected. Mortality did not associate with liver disease or any other specific disease entity. A possible mechanism for the reduced lifespan is subclinical inflammation that may be augmented by chronic viral infection. We hypothesized that chronic HBV infection contributes to this process causing a reduced life span. We added measurement of two markers of inflammation to the 10‐year follow‐up on our study of HBV among 50‐ through 69‐years‐old subjects in Greenland. The markers were YKL40 related to liver disease and hsCRP as a global marker of inflammation. Survival was evaluated using Cox regression with time until death entered as dependent variable and age, sex, smoking, alcohol intake, BMI, the presence of HBsAg and one marker of inflammation as explanatory variables. Forty‐eight percent of participants with chronic HBV infection were alive after 10 years compared with 65% of participants without infection (p = 0.003). Survival associated with age (p < 0.001), BMI (p = 0.003) and both YKL40 and hsCRP (both, p < 0.001). Harbouring HBV influenced 10‐year survival in the Cox regression after adjusting for age, sex, BMI, smoking, alcohol intake and inflammation. In conclusion, chronic low‐grade inflammation and being infected with HBV were independent markers of mortality in otherwise healthy subjects. Thus, the 7‐year shorter lifespan among Greenlanders with chronic HBV infection seems related to the long‐lasting infection. Our findings call for caution in perceiving a chronic infection as benign.